Answer:
(a) The slope of f(x) is greater than the slope of g(x)
(b) f(x) has a greater y intercept
Step-by-step explanation:
Given
[tex]\begin{array}{cc}x & {f(x)} & -1&-9&0&-1&1&7 \ \end{array}[/tex]
[tex]g(x) = 3x - 2[/tex]
Solving (a): Compare the slopes
The slope (m) of f(x) is calculated as;
[tex]m = \frac{f(x_2) - f(x_1)}{x_2 - x_1}[/tex]
This gives:
[tex]m = \frac{f(0) - f(1)}{0 - 1}[/tex]
[tex]m = \frac{f(0) - f(1)}{- 1}[/tex]
Substitute values for f(0) and f(1)
[tex]m = \frac{-1 - 7}{- 1}[/tex]
[tex]m = \frac{-8}{- 1}[/tex]
[tex]m = 8[/tex]
The slope of g(x) can be gotten using the following comparison
[tex]g(x) = mx + b[/tex]
[tex]m \to slope[/tex]
So:
[tex]g(x) = 3x -2[/tex]
[tex]m = 3[/tex]
[tex]m_{f(x)} > m_{g(x)}[/tex]
Solving (b): Compare the y intercept
y intercept is when [tex]x = 0[/tex]
From the table of f(x)
[tex]f(0) = -1[/tex]
From the equation of g(x)
[tex]g(x) = 3x -2[/tex]
[tex]g(0) = 3*0-2[/tex]
[tex]g(0) =-2[/tex]
[tex]f(0) > g(0)[/tex]